2017
DOI: 10.12659/msm.905210
|View full text |Cite
|
Sign up to set email alerts
|

Fork Head Box Class O1 (FOXO1) Activates Bim Expression to Mediate Cardiac Apoptosis in Chronic Intermittent Hypoxia-Induced Cardiac Hypertrophy

Abstract: BackgroundObstructive sleep apnea syndrome (OSAS) is characterized by chronic intermittent episodes of upper-airway obstruction with hypoxia and is associated with increased risk of cardiovascular diseases, including myocardial hypertrophy. Chronic intermittent hypoxia (CIH) has been shown to induce apoptosis in cardiomyocytes. However, the mechanisms of cardiomyocytes apoptosis under CIH largely remain unclear.Material/MethodsWe used male Sprague-Dawley rats and human cardiomyocyte cell line H9C2, and Annexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…The FOXO1 transcription factor belongs to the Forkhead family and is known as a tumour suppressor that regulates the expression of a series of cancer‐associated genes, such as cyclin D1, IGFBP‐1, p130, p27, p21, cyclin D2, FasL and Bim 27‐32 . FOXO1 participated in modulating of many biological processes, such as apoptosis, DNA damage repair, cell cycle arrest and/or oxidative stress resistance, 23 and decreased FOXO1 mRNA levels were detected in breast carcinoma, prostate cancer, osteosarcoma, hepatocellular carcinoma and Ewing sarcoma 24‐38 . Numerous signalling pathways and molecules are related to glioma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The FOXO1 transcription factor belongs to the Forkhead family and is known as a tumour suppressor that regulates the expression of a series of cancer‐associated genes, such as cyclin D1, IGFBP‐1, p130, p27, p21, cyclin D2, FasL and Bim 27‐32 . FOXO1 participated in modulating of many biological processes, such as apoptosis, DNA damage repair, cell cycle arrest and/or oxidative stress resistance, 23 and decreased FOXO1 mRNA levels were detected in breast carcinoma, prostate cancer, osteosarcoma, hepatocellular carcinoma and Ewing sarcoma 24‐38 . Numerous signalling pathways and molecules are related to glioma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of these pathological changes may be involved in Akt‐FoxO1/Bcl‐2/survivin/caspase3 signal activation 21 . Furthermore, FoxO1 can also activate Bim expression to promote chronic intermittent hypoxia‐induced apoptosis of cardiomyocytes, hypertrophy, and perivascular fibrosis 14 . Consistent with the above results, a recent study indicated that increasing phosphorylation of Akt‐FoxO1 can attenuate cardiomyocyte apoptosis and decrease the expression of N‐terminal pro brain natriuretic peptide, a marker of heart failure 22 .…”
Section: Role and Molecular Mechanism Of Foxo1 In Cardiac Hypertrophymentioning
confidence: 99%
“…calcineurin/nuclear factor of activated T cells (NFAT), muscle RING finger 1 (MuRF1)/ muscle atrophy F-box (MAFbx), pyruvate dehydrogenase kinase 4 (PDK4), and peroxisome proliferator-activated receptor α (PPARγ) coactivator-1α (PGC-1α)]. 13 Notably, FoxO1 can regulate calcium homeostasis, protein synthesis, apoptosis, and autophagy, which have been confirmed to inhibit cardiac hypertrophy in many studies 12,14 (Figure 2).…”
Section: The Foxo Familymentioning
confidence: 99%
“…Hypoxia-induced apoptosis and autophagy have been reported in myoblasts [9, 13]. OSA can evoke apoptosis in the cardiac muscle [14]. Furthermore, accumulating evidence has demonstrated that autophagy is also involved in OSA [15].…”
Section: Introductionmentioning
confidence: 99%